Figurative Language In Fiddlehead’s Album Between The Richness - Muhammad Fauzan; Juliansyah -Juliansyah; Nurul Fitriani; Kurnia Idawati; Bambang Trisno Adi (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to analyze the figurative language used in the Fiddlehead album Between the Richness. The album, known for its emotive and poetic lyrics, serves as a rich source for understanding how figurative language enhances the thematic depth of the songs. This research applies a qualitative approach to identify and categorize various types of figurative language. This research finds certain number of each type of figurative language. They are: 17 for metaphor, 7 for hyperbole, 1 for simile, 8 for imagery, 3 for paradox, 2 for oxymoron, 1 for alliteration, 1 for juxtaposition, 3 for Symbolism, 1 for synecdoche, 4 for personification, 2 for antithesis, and 2 for repetition. The most dominant type of figurative language used in the Fiddlehead song lyrics in the album Between the Richness is metaphor. The findings suggest that the use of figurative language not only intensifies the emotional impact of the music but also provides deeper insight into the experiences and perspectives shared in the album. This research highlights the role of figurative language in creating a more immersive and meaningful listening experience and offering a nuanced understanding of Fiddlehead's lyrical artistry. Keywords: Emotional; Expression; Figurative Language; Lyrics; Meaning